Targeting survivin overcomes drug resistance in acute lymphoblastic leukemia - Park, Eugene; Gang, Eun Ji; Hsieh, Yao-Te; Schaefer, Paul; Chae, Sanna; Klemm, Lars; Huantes, Sandra; Loh, Mignon; Conway, Edward M.; Kang, Eun-Suk; Hoe Koo, Hong; Hofmann, Wolf-Karsten; et al. (Blood, 2011)
Relapse of drug-resistant acute lymphoblastic leukemia (ALL) has been associated with increased expression of survivin/BIRC5, an inhibitor of apoptosis protein, suggesting a survival advantage for ALL cells. In the present study, we report that inhibition of survivin in patient-derived ALL can eradicate leukemia. Targeting survivin with shRNA in combination with chemotherapy resulted in no detectable minimal residual disease in a xenograft model of primary ALL. Similarly, pharmacologic knock-down of survivin using EZN-3042, a novel locked nucleic acid antisense oligonucleotide, in combination with chemotherapy eliminated drug-resistant ALL cells. These findings show the importance of survivin expression in drug resistance and demonstrate that survivin inhibition may represent a powerful approach to overcoming drug resistance and preventing relapse in patients with ALL.
Gesehen am 09.09.2022